Integritas Kebenaran Akuntan Publik di KAP "ABC" Surabaya (Studi Fenomenologi) - Aripratiwi, Ratna Anggraini (AKTSAR: Jurnal Akuntansi Syariah, 2020)
This study aims to obtain a deep meaning for public accountant integrity in Public Accounting Firm “ABC” Surabaya through a phenomenology approach. Revealing public accountants' integrity because of the many public accountants is still dragged into fraud and violations, resulting in unethical decisions. Every public accountant has a different perspective in determining and exercising an integrity attitude, whether to defend or even take it off for a particular purpose. And in the end, bring up a variety of diverse meanings of pure integrity and pragmatic integrity.